2010
DOI: 10.1016/j.drugalcdep.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil does not serve as a reinforcer in cocaine abusers

Abstract: The purpose of this double-blind, randomized, outpatient study was to evaluate the reinforcing and subjective effects of modafinil (200, 400, or 600 mg) in cocaine-abusers. Twelve participants (2 Female, 10 Male) completed this study, consisting of 3 blocks of 7 sessions; each block tested a difference dose of modafinil. During the first 2 sessions of each block, participants “sampled” 1 of the doses of modafinil, and placebo. This dose of modafinil and placebo were available for the subsequent five choice ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Stoops et al (2005) reported that modafinil served as a reinforcer in human volunteers performing a cognitive task, although not when they were relaxing. However, the weakness of modafinil's reinforcing effect relative to cocaine was demonstrated by its failure to serve as a positive reinforcer in stimulant abusers (Rush et al, 2002b;Vosburg et al, 2010) and its lack of clinical efficacy in the treatment of cocaine dependence, showing that it has low reinforcing effects of its own (Anderson et al, 2009). Lisdexamfetamine did not maintain intravenous selfadministration at levels greater than saline when tested across a range doses indicating that this prodrug does not serve as a positive reinforcer in cocaine-trained rats.…”
Section: Discussionmentioning
confidence: 99%
“…Stoops et al (2005) reported that modafinil served as a reinforcer in human volunteers performing a cognitive task, although not when they were relaxing. However, the weakness of modafinil's reinforcing effect relative to cocaine was demonstrated by its failure to serve as a positive reinforcer in stimulant abusers (Rush et al, 2002b;Vosburg et al, 2010) and its lack of clinical efficacy in the treatment of cocaine dependence, showing that it has low reinforcing effects of its own (Anderson et al, 2009). Lisdexamfetamine did not maintain intravenous selfadministration at levels greater than saline when tested across a range doses indicating that this prodrug does not serve as a positive reinforcer in cocaine-trained rats.…”
Section: Discussionmentioning
confidence: 99%
“…Because DAT inhibitors and releasers both increase extracellular DA concentration, it was originally assumed that all drugs interacting with DAT would induce behavioral effects identical to a prototypical DAT inhibitor such as cocaine (e.g., readily self-administered, locomotor-stimulating properties, and shared discriminative properties). Although a multitude of DAT inhibitors that have cocaine-like properties exist (e.g., RTI55 [methyl-(1R,2S,3S)-3-(4-iodophenyl)-8-methyl-8-azabicyclo (Søgaard et al, 1990;Carroll et al, 2009;Vosburg et al, 2010). One problem with using traditional DAT inhibitors for stimulant abuse treatment is that these inhibitors also have abuse liability and the potential to enhance the effects of abused drugs (see Barrett et al, 2004;Hiranita et al, 2011 (Desai et al, 2005b;Li et al, 2011), demonstrating that the reinforcing effects of a drug are not solely a property of actions at DAT or that these inhibitors have a different manner of interaction with DAT (see below).…”
Section: Pharmacological Manipulation Of the Dopamine Transportermentioning
confidence: 99%
“…However, a multitude of studies conducted over the past 10-15 years indicate that this notion is incorrect: although certain DAT inhibitors do produce the anticipated cocaine-like behavioral reactions, various atypical DAT inhibitors, such as benztropine, modafinil, and vanoxerine (GBR12909; 1-(2-[bis(4-fluorophenyl)methoxy]ethyl)-4-(3-phenylpropyl)-piperazine), have far milder reinforcing and locomotor stimulant properties, particularly in humans (Søgaard et al, 1990;Carroll et al, 2009;Vosburg et al, 2010). Moreover, exceptionally potent dopamine uptake inhibitors that exhibit no reinforcement efficacy in animal models have also been reported, indicating that addictiveness is not a constant property of DAT inhibitors (Desai et al, 2005;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%